Phaeochromocytoma in children. Issue 10 (22nd May 2008) - Armstrong, R; Sridhar, M; Greenhalgh, K L; Howell, L; Jones, C; Landes, C; McPartland, J L; Moores, C; Losty, P D; Didi, M
Abstract : Phaeochromocytoma is a rare clinical entity in children. Contrary to traditional teaching, which suggested that 10% of phaeochromocytomas are "familial", a germline mutation has been identified in up to 59% (27/48) of apparently sporadic phaeochromocytomas presenting at 18 years or younger and in 70% of those presenting before 10 years of age. The inherited predisposition may be attributable to a germline mutation in the Von Hippel–Lindau gene, the genes encoding the subunits B and D of succinate dehydrogenase, the RET proto-oncogene predisposing to multiple endocrine neoplasia type 2, or the neurofibromatosis type 1 gene. Of these, the Von Hippel–Lindau gene is the most commonly mutated gene in children presenting with a phaeochromocytoma. Genetic counselling is recommended before gene testing and investigation of the wider family. This review provides guidance on the aetiology, investigation, management, histopathology, genetics and follow-up of children with a phaeochromocytoma.